Nephrogenic rests in Wilms tumors treated with preoperative chemotherapy: The UK SIOP Wilms Tumor 2001 Trial experience. Issue 11 (6th April 2017) - Vujanić, Gordan M.; Apps, John R.; Moroz, Veronica; Ceroni, Federica; Williams, Richard D.; Sebire, Neil J.; Pritchard‐Jones, Kathy
Abstract: Background: Nephrogenic rests (NRs) are abnormally persistent foci of embryonal cells, thought to be the precursor lesion of Wilms tumors (WTs). To date, their presence has not been systematically examined in WTs treated with preoperative chemotherapy. Methods: A systematic analysis of the data on NRs in WTs treated with preoperative chemotherapy obtained from the UK cohort of the International Society of Pediatric Oncology (SIOP) WT 2001 Trial. The study was based on central pathology review of full sets of slides from pathological specimens, with a median of 28 slides reviewed per case. Results: NRs were identified in 40% of unilateral WTs, including 25% perilobar nephrogenic rest (PLNR), 9% intralobar nephrogenic rest (ILNR), 5% both PLNR and ILNR, and 1% nephroblastomatosis, and in 93% of cases with bilateral lesions. ILNRs were associated with stromal histology and a younger age at diagnosis and found frequently in patients with congenital anomalies associated with WT1 mutation. PLNRs were found frequently in patients with overgrowth syndromes. Conclusions: The prevalence of NRs in WTs after preoperative chemotherapy observed in SIOP UK WT 2001 Trial is similar to the previously published data on NRs not treated with preoperative chemotherapy. Their epidemiology supports at least two pathways to Wilms tumorigenesis.